2003
DOI: 10.1001/archsurg.138.6.619
|View full text |Cite
|
Sign up to set email alerts
|

Upstaging of Atypical Ductal Hyperplasia After Vacuum-Assisted 11-Gauge Stereotactic Core Needle Biopsy

Abstract: Background: Nonpalpable mammographic abnormalities are frequently evaluated by means of a stereotactic core needle biopsy. This technique is a very sensitive indicator of invasive cancer, but is less reliable to discriminate between ductal carcinoma in situ and atypical ductal hyperplasia (ADH). The objective of this study was to determine the correlation of the 11-gauge vacuumassisted core needle biopsy to open biopsy when a diagnosis of ADH is obtained. Hypothesis: The use of 11-gauge vacuum-assisted stereot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
4
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 18 publications
4
35
4
4
Order By: Relevance
“…Jackman et al (16) reported that the underestimation of malignant disease increased with VAB when the number of cores obtained per lesion was 10 or less. However, other authors did not confirm these findings (23,29). In this study, there was no difference between the group that received an accurate diagnosis and the underestimated group with US-guided 14-gauge core needle biopsy and 11-gauge SVAB in terms of the number of core specimens obtained.…”
Section: Discussioncontrasting
confidence: 68%
“…Jackman et al (16) reported that the underestimation of malignant disease increased with VAB when the number of cores obtained per lesion was 10 or less. However, other authors did not confirm these findings (23,29). In this study, there was no difference between the group that received an accurate diagnosis and the underestimated group with US-guided 14-gauge core needle biopsy and 11-gauge SVAB in terms of the number of core specimens obtained.…”
Section: Discussioncontrasting
confidence: 68%
“…1 This would indicate that excision is more often not warranted, but there are still no clear guidelines for the management of patients when epithelial atypia are diagnosed at microbiopsy. Up until now, most reports published in the literature [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have focused on underestimation of lesions at microbiopsy when compared with surgical excisions. Some authors have identified patients who should or should not be spared surgery when epithelial atypia were diagnosed at microbiopsy performed for microcalcifications, but criteria to excise or not differ according to the authors.…”
mentioning
confidence: 99%
“…For these reasons, lesions determined to be ADH at core needle biopsy often are found to be malignant tumors at subsequent surgery [7,8]. Reports [9][10][11][12][13][14][15][16] indicate a 20-56% rate of underestimation of ADH at stereotactic 14-gauge automated core biopsy and a 11-27% rate at stereotactic 11-gauge vacuum-assisted biopsy. Because most lesions containing ADH have calcifications, underestimation at percutaneous biopsy is most common for calcific lesions examined with stereotactic biopsy [17].…”
mentioning
confidence: 99%